Genome-wide identification of the MIKCc-type MADS-box gene family in Chrysanthemum lavandulifolium reveals their roles in the capitulum development - Li, Junzhuo; Zhang, Qiuling; Kong, Deyuan; Pu, Ya; Wen, Xiaohui; Dai, Silan (Frontiers in Plant Science, 2023)
Abstract: Chrysanthemum ×morifolium is well known throughout the world for its diverse and exquisite flower types. However, due to the complicated genetic background of C. ×morifolium, it is difficult to understand the molecular mechanism of its flower development. And it limits the molecular breeding of improving chrysanthemum flower types. C. ×morifolium has the typical radial capitulum, and many researches showed that the members of the MIKCc-type MADS box gene family play a key role in the formation and development of the capitulum. However, it has been difficult to isolate the important MIKCc and investigate their roles in this process due to the lack of genomic information in chrysanthemum. Here, we identified MIKCc-type MADS box genes at whole genome-wide level in C. lavandulifolium, a diploid species closely related to C. ×morifolium, and investigated their roles in capitulum development by gene expression pattern analysis and protein interaction analysis. A total of 40 ClMIKCc were identified and were phylogenetically grouped into 11 clades. Members of all clades showed different enriched expression patterns during capitulum formation. We speculate that the E-class genes in C. lavandulifolium underwent subfunctionalization because they have a significantly expanded, more diverse expression patterns, and specifically tissue expression than AtSEPs. Meanwhile, we detected the C-class expressed in disc floret corolla, which could be the clue to explore the morphological differences between disc and ray floret corolla. In addition, the potential roles of some MIKCcs in complex inflorescence formation were explored by comparing the number and phylogenetic relationship of MIKCc subfamily members in Asteraceae with different capitulum types. Members of the FLC branch in Asteraceae were found to be possibly related to the differentiation and development of the ray floret.